The care of the elderly with diabetic nephropathy in conservative treatment - Caren da Silva Jacobi; Margrid Beuter; Claudia Regina Maldaner; Camila Castro Roso; Macilene Regina Pauletto; Nara Marilene Oliveira Girardon-Perlini (Universidade Federal do Ceará, 2013)
This study aimed to describe the care of the elderly and the participation of the family in the conservative treatment of diabetic nephropathy. This is a qualitative, descriptive and exploratory study developed with twelve people, from which six were elderly patients with diabetic nephropathy in conservative treatment, followed in a nephrology ambulatory and a family member. Data collection occurred from August to October 2011 using semi-structured interviews. Data were subjected to thematic analysis. The results highlighted the need of adaptation and restrictions in eating routine, of control and knowledge of treatment and medicine and inclusion of family members in the treatment of the elderly. Thus, the elderly with diabetic nephropathy in conservative treatment and their families experienced care permeated by difficulties. So, they require professional help to have enough knowledge to understand and adhere to this treatment.